Mapping the landscape of academic integrity education programs: what approaches are effective?. Issue 1 (2nd January 2020) - Sefcik, Lesley; Striepe, Michelle; Yorke, Jonathan
Abstract: Research has shown that academic integrity education programs can have a positive impact on student attitudes and reduce breaches of academic integrity. Although programs vary across institutions, there is relatively little research on their comparative efficacy. Accordingly, this study examines how higher education institutions in Australia and New Zealand approach academic integrity education in order to identify particular features that are considered to be most effective. Forty-four institutions are represented in this research, with data collected via a survey and semi-structured interviews with selected participants. The findings reveal that, in many cases, current academic integrity education programs appear to lack comprehensive information on values, the potential risks to integrity and the pitfalls of assessment outsourcing. Instead, curricula tended to focus on plagiarism, student responsibilities and referencing. Institutions employ a range of different communication and administration strategies to encourage uptake, and it was found that centrally administered programs that employed sanctions for non-completion appeared to be the most effective method for achieving compliance. Whilst the use of sanctions may support completion, it is argued that future academic integrity programs should also be collaboratively designed, drawing on a timely educational approach for skill development that incorporates learner feedback into the process with a greater emphasis on underpinning values.